Analisis Kesiapan Industri Kreatif Menghadapi AEC 2015 Menggunakan Metode Regresi Linier Berganda(Studi Kasus: Kecamatan Pasar Kliwon Kota Surakarta) - Andriyoso, Agus, Mila Faila Sufa, S.T., M.T, Much. Djunaidi, S.T., M.T (2015)
Creative industries in 2015 became one of the pioneers of a country to face the competition at the international level, particularly in Southeast Asia, including Indonesia at the end of 2015 will face Peoples, Asean Economics community (AEC). Chance or even challenge for the Indonesian people, especially entrepreneurs in facing the MEA. evaluation in the creative industry sector which is one of the keys in the face of MEA should be dug and prepared in all aspects of legality, standardization, capital and improving labor skills. Creative industries in 2015 became one of the pioneers of a country to face the competition at the international level, particularly in Southeast Asia, including Indonesia at the end of 2015 will face Peoples, Asean Economics (MEA). Chance or even challenge for the Indonesian people, especially entrepreneurs in facing the MEA. evaluation in the creative industry sector which is one of the keys in the face of MEA should be dug and prepared in all aspects of legality, standardization, capital and improving labor skills. Several hypotheses related to the readiness of labor and capital creative industry, especially in Pasar Kliwon Market Surakarta on preparedness AEC 2015, became one of the topics pembahsaan very crucial considering the AEC in sight. therefore, several hypotheses related to the creative industries, namely the labor and capital that will test its effect on the readiness of the creative industry of the AEC. using Regression and use the f and t test to determine the significance of the hypothesis that the effect on the readiness of the creative industries in the face of the Asean Economic Community (AEC). Creative industries in 2015 became one of the pioneers of a country to face the competition at the international level, particularly in Southeast Asia, including Indonesia at the end of 2015 will face Peoples, Asean Economics (MEA). Chance or even challenge for the Indonesian people, especially entrepreneurs in facing the MEA. evaluation in the creative industry sector which is one of the keys in the face of MEA should be dug and prepared in all aspects of legality, standardization, capital and improving labor skills. Several hypotheses related to the readiness of labor and capital creative industry, especially in Pasar Kliwon Market Surakarta on preparedness AEC 2015, became one of the topics pembahsaan very crucial considering the AEC in sight. therefore, several hypotheses related to the creative industries, namely the labor and capital that will test its effect on the readiness of the creative industry of the AEC. using Regression and use the f and t test to determine the significance of the hypothesis that the effect on the readiness of the creative industries in the face of the Asean Economic Community (AEC). The research result analysis Regression showed variable Labor and Capital affect the readiness of the creative industries in the face of the AEC, but the results of the t test or partially showed labor significant influence, it can show the count of the t test for variable labor thitung > t table (2.760> 2.042), meaning that the first hypothesis (H1) has a significant influence on the readiness of the creative industries in the face of the AEC. While in the capital variables showed tcount <t table (0.335 <2.042) means that the second hypothesis (H2) did not significantly influence the readiness in the face of the .